MODEL PBL BERDIFERENSIASI DITINJAU DARI GAYA BELAJAR UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Rachmawati, Indah; Agustini, Ferina; Yani, Esti (Prodi Pendidikan Guru Sekolah Dasar (PGSD) FKIP Universitas Pattimura, 2025)
The strategy to future challenges includes preparing quality learning. One of the main factors that define quality learning is the improvement of students learning outcomes. Therefore, the author intends to conduct an experiment to improve learning outcomes in the subject of Pancasila Education. This experiment uses the PBL model, considering the students' learning styles. The subjects of this study are the fifth-grade students of SDN Pandeanlamper 03 Semarang, consisting of 27 students, with a mixed-method research approach combining both quantitative and qualitative methods. This research uses the One-Group Pretest-Posttest Design concept, with data collection techniques involving numerical data obtained through pre-test and post-test activities conducted before and after the implementation of the PBL model, considering learning styles. The results of the research show that there was an improvement in students' learning outcomes. The pretest results showed an average class score of 68, while the posttest average increased to 86.5. After analyzing the data using N-Gain, the result obtained was 0.6054, which falls into the medium category. Therefore, it can be concluded that learning using the PBL model, considering learning styles, is effective in improving the learning outcomes of the fifth-grade students at SDN Pandeanlamper 03 Semarang.